(untitled) - Chow, Ven Te (New York, 1988)
The book presents and describes surfacewater hydrology in three sections: Hydrologic processes, Hydrologic analysis, Hydrologic design. The book also contains 90 examples solved and 400 additional problems presented at the end of chapter homework or self-study
Keywords: Hydrology